2014
DOI: 10.1371/journal.pone.0091435
|View full text |Cite
|
Sign up to set email alerts
|

Dre - Cre Sequential Recombination Provides New Tools for Retinal Ganglion Cell Labeling and Manipulation in Mice

Abstract: BackgroundGenetic targeting methods have greatly advanced our understanding of many of the 20 Retinal Ganglion Cell (RGC) types conveying visual information from the eyes to the brain. However, the complexity and partial overlap of gene expression patterns in RGCs call for genetic intersectional or sparse labeling strategies. Loci carrying the Cre recombinase in conjunction with conditional knock-out, reporter or other genetic tools can be used for targeted cell type ablation and functional manipulation of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 76 publications
(87 reference statements)
5
40
0
Order By: Relevance
“…Both Brn3c CKOCre (in CAG:Dre; Brn3c CKOCre ; Rosa26 AP mice) and Brn3c Cre in Brn3c Cre ; Rosa26 tdTomato mice) drive Cre expression almost exclusively in Brn3c + cells (~91% of AP positive cells are Brn3c + - Figure 2m1, p1, and ~ 99 % of tdTomato positive cells are Brn3c + Figure 3e, g). As previously reported (Anastassiadis et al, 2009;Sajgo et al, 2014), Dre is not inducing any recombination of the Cre reporter Rosa26 AP as both retinas (Figure 2d, j) and brains (Figure 8a-a4) of CAG:Dre; Rosa26 AP mice are completely devoid of AP staining. The Cre recombinase expression correctly reproduces the expression of Brn3c, either after inversion-excision mediated by Dre ( Figure 1h), or in constitutive knock-in configuration (Figure 1i).…”
Section: Sequential Dre To Cre Recombination At the Brn3c Locussupporting
confidence: 84%
See 1 more Smart Citation
“…Both Brn3c CKOCre (in CAG:Dre; Brn3c CKOCre ; Rosa26 AP mice) and Brn3c Cre in Brn3c Cre ; Rosa26 tdTomato mice) drive Cre expression almost exclusively in Brn3c + cells (~91% of AP positive cells are Brn3c + - Figure 2m1, p1, and ~ 99 % of tdTomato positive cells are Brn3c + Figure 3e, g). As previously reported (Anastassiadis et al, 2009;Sajgo et al, 2014), Dre is not inducing any recombination of the Cre reporter Rosa26 AP as both retinas (Figure 2d, j) and brains (Figure 8a-a4) of CAG:Dre; Rosa26 AP mice are completely devoid of AP staining. The Cre recombinase expression correctly reproduces the expression of Brn3c, either after inversion-excision mediated by Dre ( Figure 1h), or in constitutive knock-in configuration (Figure 1i).…”
Section: Sequential Dre To Cre Recombination At the Brn3c Locussupporting
confidence: 84%
“…The same retinorecipient areas labeling is observed in the CAG:Dre; Brn3c CKOCre/WT ; ROSA26 AP/WT brains (Figure 8 b-b4), however several other thalamic and brainstem areas are stained, presumably reflecting extraretinal expression of Brn3c (see below). No AP staining was seen in CAG:Dre; ROSA26 AP/WT brains, further confirming that there is no cross-reactivity between the Dre recombinase and the loxP target sites (Anastassiadis et al, 2009;Sajgo et al, 2014) (Figure 8a-a4). We note that significant amounts of AP staining are seen in Brn3c CKOCre/WT ; ROSA26 AP/WT brains, further suggesting that the Cre recombinase is also transcribed/translated in the inverted configuration (Fuller and Badea, data not shown).…”
Section: Brn3c Cre Rgc Projections To Retinorecipient Areasmentioning
confidence: 62%
“…The vertebrate retina, with its three cellular layers and six neuronal classes, has been a useful model for studying general principles of neurogenesis and axon guidance. Each class of retinal cells can be further divided into morphologically and functionally distinct subtypes, and recent efforts have identified the molecular programs that establish these differences within neuronal classes, such as amacrine, bipolar, and retinal ganglion cell (RGC) subtypes (Kim et al, 2008; Badea et al, 2009; Kay et al, 2011a, 2011b; Watson et al, 2012; Jiang et al, 2013; Sajgo et al, 2014; Macosko et al, 2015; Osterhout et al, 2015; Sanes and Masland, 2015; Tang et al, 2015; Jin et al, 2015; Rousso et al, 2016; Shekhar et al, 2016). RGCs, as the only projection neurons of the retina, can be additionally distinguished by the laterality of their axonal projection to targets in the thalamus and midbrain.…”
Section: Introductionmentioning
confidence: 99%
“…It is a close homolog of Cre, but has similar recombination efficiency and specificity for its own target sites, while exhibiting no cross-reactivity with the other well established recombinases, Cre and Flp. Several mouse and zebrafish models have been developed and validated demonstrating both the feasibility of Dre recombination in genetic manipulations and its use in combinatorial approaches with other recombinases ( Anastassiadis et al 2009 ; Park and Leach 2013 ; Fenno et al 2014 ; Sajgo et al 2014 ; Madisen et al 2015 ). Some of these studies have reported a moderate level of cross-talk between Dre and Cre, especially in the context of viral delivery of the recombinases and targets.…”
mentioning
confidence: 99%